Theoretical and practical aspects of implementation of biomechanical principles of organization of moving motions in sports - Янис Ланка; Владимир Гамалий (National University of Physical Education and Sport of Ukraine, 2017)
The paper analyzes and summarizes the theoretical information about implementation of biomechanical principles of organization of moving motions in sports with a view to their practical use in everyday coaching practice. Biomechanical principles, the general conditions for organization of coordination structure of movements, are based on the laws of physics and biology. The fragments of realization of throwing and kicking movements in sports are provided as practical examples, because they are based on the general mechanism of acceleration of distal links of a kinematic chain and have nearly identical features of its functioning. The provided information allows a practical coach to understand deeply the essence of technique ele ments of moving motions and of all the action as a whole, which will improve the quality of technical preparation of athletes at all stages of sporting advancement.